PENGUJIAN SUBSTANTIF ATAS AKUN PIUTANG USAHA PADA KAP JEPTHA NASIB DAN JUNIHOL (KASUS PADA PT.XYZ) - Ayu Nopiyanti (2021)
Auditing is one of the service activities in which the process of conducting a gradual inspection and evaluation of the company's financial statements at a certain period within one year. This is done in order to assess whether the financial statements have been prepared based on generally accepted accounting principles. Every year the company needs to make an audit request to the public accounting firm so that the management can find out whether there is an error in the financial statements that have been made by the company. In the audit process, the auditor determines the level of materiality where it is a major part of the financial statements and determines the tolerable misstatement of certain accounts or classes of transactions. Substantive testing is the last process at KAP JNJ in the audit examination stage. This test aims to examine and analyze the financial statements in detail on the accounts that affect the fairness of the financial statements of PT. XYZ. The substantive test carried out this time is a substantive test of the accounts receivable account which aims to determine the existence of a misstatement of receivables from the amount that should be. The implementation of this street vendor is carried out in order to implement the theory obtained during the lecture period and applied in the public accounting firm Jeptha fate and junihol. This activity also provides experience to writers in developing skills and work ethics.